Pengaruh Kemampuan dan Motivasi Kerja Terhadap Kinerja Karyawan di Hotel Isola Resort & Meeting Services - Aprilia, Lu’luwatin Rosdiana (Universitas Pendidikan Indonesia, 2018)
ASEAN Economic Community (AEC) is a major issue in the world of tourism, especially for the hospitality industry. The quality of human resources becomes essential aspects in order to face the AEC, therefore employee performance is very important to note the suitability those performance low can be influenced by some issues ability and motivation work employees. The aim of this research is to find out how the work ability and motivation give or affect the performance of employees di Hotel Isola. The method used in this research is explanatory survey method. Samples were frontline employees as much as 40 respondents by stratified random sampling. Data were analyzed by by using path analysis with SPSS V.22.0 The results showed that there is influence between the variables of work ability and variable work motivation on employee performance.